2023
DOI: 10.1039/d2tb02714c
|View full text |Cite
|
Sign up to set email alerts
|

Visible label-free detection of bacterial DNA using flocculation of sterically stabilised cationic latexes

Abstract: The current gold standard diagnostic for bacterial infections is the use of culture, which can be time consuming and can take up to five days for results to be reported....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…These positive results expand upon previous demonstrations from our group showing flocculation in response to amplified DNA from Pseudomonas aeruginosa, a Gram-negative bacterium. 30 Importantly, the PEGMA-P2VP latexes did not show any visual signs of flocculation on the addition of either the DNA extraction reagents or the HSV-2 Mastermix (Figure SI3). Bridging flocculation requires macromolecules (DNA in this case) to be of a certain molecular weight, and the dNTPs, primers and salts present in these mixtures are not of a sufficient molar mass to induce flocculation of the PEGMA-P2VP latex despite having some negative charge or inducing charge screening.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These positive results expand upon previous demonstrations from our group showing flocculation in response to amplified DNA from Pseudomonas aeruginosa, a Gram-negative bacterium. 30 Importantly, the PEGMA-P2VP latexes did not show any visual signs of flocculation on the addition of either the DNA extraction reagents or the HSV-2 Mastermix (Figure SI3). Bridging flocculation requires macromolecules (DNA in this case) to be of a certain molecular weight, and the dNTPs, primers and salts present in these mixtures are not of a sufficient molar mass to induce flocculation of the PEGMA-P2VP latex despite having some negative charge or inducing charge screening.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lightly cross-linked, PEGMA-P2VP with a mean diameter of approximately 700 nm was prepared by conventional emulsion polymerization to yield latex particles with a nonionic steric stabilizer and cationic core (Figure SI1). This latex was used in all subsequent studies reported herein …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations